Management of recurrent phyllodes with full thickness chest wall resection - Awwal, R; Shashi, SA; Khondokar, MS; Khundkar, SH (Bangladesh Journal of Plastic Surgery, 2010)
Phyllodes tumours are biphasic fibroepithelial neoplasms of the breast and each case represents a unique challenge. Even after apparent wide local excision of benign lesions, they recur and recurrences can occur even for 5-6 times. The ultimate end result is chest wall invasion and reconstruction then becomes an essential part of the curative surgical procedure. For a locally advanced breast malignancy, treatment is always palliative with simple coverage and oncologic support. But as Phyllodes tumour is of low aggressiveness, wide excision of even locally advanced malignant phyllodes can result in a good prognosis. Wide and extensive resection always invites the need of reconstruction, and surely it is a challenge when it is for a post-mastectomy recurrent lesion, where the role of plastic surgeons becomes essential. Two such cases are presented where disease control was only possible after full thickness chest wall resection. DOI: http://dx.doi.org/10.3329/bdjps.v1i1.6486 Bangladesh Journal of Plastic Surgery (2010) Vol. 1 (1) pp.9-13